(untitled) (Global Journal of Science Frontier Research, 2020)
In this paper,we first characterize the boundedness of the condition under which composite multiplication pre-frame operators on L 2 (μ) -space, namely M u,T,f and its adjoint. Then, we identify the relation between the adjoint of M u,T,f and the composite multiplication frame operators which is denoted by S u,T,f all the results have been obtained in terms of radonnikodymderivative h T .